Global, regional, and national burden of laryngeal cancer attributable to smoking, 1990–2021, and projections to 2036: a systematic analysis of the Global Burden of Disease study 2021 - Shi, Liangwen; Kuang, Zhixing; Tu, Jiannan; Wang, Taiqin; Liu, Tao; Liu, Jingbo; Liu, Jianzhi (Frontiers in Public Health, 2025)
BackgroundLaryngeal cancer, predominantly linked to smoking, persists as a formidable global health challenge. Acquiring a deeper understanding of laryngeal cancer attributable to smoking (LCAS) burden and trends is essential for crafting nuanced and impactful prevention and intervention strategies.MethodsThe Disability-Adjusted Life Years (DALYs), mortality, and corresponding Age-Standardized DALY rate (ASDR) and Age-Standardized Mortality Rate (ASMR) were systematically evaluated using the GBD 2021 data. Temporal trends were characterized through Joinpoint regression analysis, while the influence of socioeconomic factors on disease distribution and the associated disparities was probed through correlation analysis. Decomposition analysis was employed to identify the key factors driving changes in DALY and mortality burdens, and the Bayesian Age-Period-Cohort (BAPC) model was used to project future trends.ResultsOver the past 30 years, the global burden of LCAS, as measured by DALYs and the number of deaths, has remained relatively stable with a modest increase of approximately 20.8 and 11.53%, respectively. However, both ASDR and ASMR have shown a decline, from 44.42 to 23.38 and from 1.61 to 0.89, respectively. Regionally, the burden is predominantly concentrated in Asia, Europe, as well as North Africa and the Middle East. In all regions, both ASDRs and ASMRs are on a downward trajectory, with the rate of decline being more pronounced as socio-economic indices (SDI) rise. Notably, Australasia, High-income Asia Pacific, and Western Europe exhibit the largest annual reductions in ASDRs and ASMRs. Population aging has been identified as the primary driver of DALYs and mortality burden in High-income Asia Pacific, while population growth plays a more significant role in other regions. In the next 15 years, both ASDR and ASMR are expected to continue their decline.ConclusionDespite progress in reducing LCAS rates over 30 years, regional disparities persist, strengthened tobacco control measures are essential to further alleviate the LCAS burden and reduce smoking-related mortality.